Nail changes in pemphigus and bullous pemphigoid: A single-center study in China - Cao, Shan; Cui, Xiaochen; Li, Jianke; Pan, Futang; Yan, Xiaoxiao; Yang, Qing; Chen, Mingfei; Zhou, Shengji; Du, Donghong; Wang, Weiwei; Sun, Yuanhang; Shi, Zhongxiang; et al. (Frontiers in Medicine, 2022)
Pemphigus and bullous pemphigoid (BP) are common types of autoimmune bullous diseases (AIBD) caused by essentially IgG autoantibodies against the structural proteins of the desmosomes at cell-cell junctions and the hemidesmosomes at epidermal-dermal junctions, respectively. Few studies have assessed nail changes in patients with pemphigus or BP. In the present study, we collected the clinical data of 191 patients with AIBD (108 patients with pemphigus and 83 patients with BP) and 200 control subjects. Nail changes were observed in 77.0% (147/191), 77.8%(84/108), and 75.9%(63/83) of patients with AIBD, pemphigus, and BP, respectively, and 14.5%(29/200) of control subjects. Beau’s lines and paronychia were the most common nail involvement, observed in 22.5% (43/191) and 22.5% (43/191) of patients with AIBD, 25.0% (27/108) and 25.9% (28/108) of patients with pemphigus, 19.3% (16/83) and 18.1% (15/83) patients with BP, respectively. The autoimmune bullous skin disorder intensity score (ABSIS) and onset time of pemphigus or BP patients with nail changes were different. Onychomycosis accounted for 21.5% (41/191) of all patients with AIBD. The ABSIS was correlated with nail involvement in patients with BP (r=0.46, P<0.001), and weakly correlated with nail involvement in patients with AIBD (r=0.37, P<0.001), pemphigus (r=0.29, P=0.009), and pemphigus vulgaris (r=0.35, P=0.008). No correlation was observed between nail involvement and antibody titers for the diseases. In conclusion, nail changes are frequently observed in patients with pemphigus and BP. The type and onset time of nail changes may indicate the severity of pemphigus and BP, which warrants dermatologists' attention.